Black Hole - Moving Mirror II: Particle Creation - Good, Michael R.R.; Anderson, Paul R.; Evans, Charles R. (My University, 2016)
There is an exact correspondence between the simplest solution to Einstein's equa- tions describing the formation of a black hole and a particular moving mirror tra- jectory. In both cases the Bogolubov coe cients in 1+1 dimensions are identical and can be computed analytically. Particle creation is investigated by using wave packets. The entire particle creation history is computed, incorporating the early- time non-thermal emission due to the formation of the black hole (or the early-time acceleration of the moving mirror) and the evolution to a Planckian spectrum
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; black holes